L-(+)-Lactic acid production by Lactobacillus rhamnosus B103 from dairy industry waste - Bernardo, Marcela Piassi [UNESP]; Coelho, Luciana Fontes [UNESP]; Sass, Daiane Cristina [UNESP]; Contiero, Jonas [UNESP] (Springer Nature, 2016)
Lactic acid, which can be obtained through fermentation, is an interesting compound because it can be utilized in different fields, such as in the food, pharmaceutical and chemical industries as a bio-based molecule for bio-refinery. In addition, lactic acid has recently gained more interest due to the possibility of manufacturing poly(lactic acid), a green polymer that can replace petroleum-derived plastics and be applied in medicine for the regeneration of tissues and in sutures, repairs and implants. One of the great advantages of fermentation is the possibility of using agribusiness wastes to obtain optically pure lactic acid. The conventional batch process of fermentation has some disadvantages such as inhibition by the substrate or the final product. To avoid these problems, this study was focused on improving the production of lactic acid through different feeding strategies using whey, a residue of agribusiness. The downstream process is a significant bottleneck because cost-effective methods of producing high-purity lactic acid are lacking. Thus, the investigation of different methods for the purification of lactic acid was one of the aims of this work. The pH-stat strategy showed the maximum production of lactic acid of 143.7 g/L. Following purification of the lactic acid sample, recovery of reducing sugars and protein and color removal were 0.28%, 100% and 100%, respectively.
Keywords: Feed strategies; Lactic acid production; Lactobacillus and lactic acid purification